What is a preferred angiotensin II receptor blocker-based combination therapy for blood pressure control in hypertensive patients with diabetic and non-diabetic renal impairment? - Mallat, Samir G (BioMed Central, 2012)
Hypertension has a major associated risk for organ damage and mortality, which is further heightened in patients with prior cardiovascular (CV) events, comorbid diabetes mellitus, microalbuminuria and renal impairment. Given that most patients with hypertension require at least two antihypertensives to achieve blood pressure (BP) goals, identifying the most appropriate combination regimen based on individual risk factors and comorbidities is important for risk management. Single-pill combinations (SPCs) containing two or more antihypertensive agents with complementary mechanisms of action offer potential advantages over free-drug combinations, including simplification of treatment regimens, convenience and reduced costs. The improved adherence and convenience resulting from SPC use is recognised in updated hypertension guidelines. Despite a wide choice of SPCs for hypertension treatment, clinical evidence from direct head-to-head comparisons to guide selection for individual patients is lacking. However, in patients with evidence of renal disease or at greater risk of developing renal disease, such as those with diabetes mellitus, microalbuminura and high-normal BP or overt hypertension, guidelines recommend renin-angiotensin system (RAS) blocker-based combination therapy due to superior renoprotective effects compared with other antihypertensive classes. Furthermore, RAS inhibitors attenuate the oedema and renal hyperfiltration associated with calcium channel blocker (CCB) monotherapy, making them a good choice for combination therapy. The occurrence of angiotensin-converting enzyme (ACE) inhibitor-induced cough supports the use of angiotensin II receptor blockers (ARBs) for RAS blockade rather than ACE inhibitors. In this regard, ARB-based SPCs are available in combination with the diuretic, hydrochlorothiazide (HCTZ) or the calcium CCB, amlodipine. Telmisartan, a long-acting ARB with preferential pharmacodynamic profile compared with several other ARBs, and the only ARB with an indication for the prevention of CV disease progression, is available in two SPC formulations, telmisartan/HCTZ and telmisartan/amlodipine. Clinical studies suggest that in CV high-risk patients and those with evidence of renal disease, the use of an ARB/CCB combination may be preferred to ARB/HCTZ combinations due to superior renoprotective and CV benefits and reduced metabolic side effects in patients with concomitant metabolic disorders. However, selection of the most appropriate antihypertensive combination should be dependent on careful review of the individual patient and appropriate consideration of drug pharmacology.